The role of the sound of objects in object identification: evidence from picture naming - Mulatti, Claudio; Treccani, Barbara; Job, Remo (Frontiers in Psychology, 2014)
In the present work we were concerned with the role of sound representations in object recognition. In order to address this issue we made use of a picture naming task in which target pictures might be accompanied by a white-noise burst. White-noise was thought to interfere with the representation of the sound possibly associated with the depicted object. We reasoned that if such a representation is critical for the recognition of objects strongly associated with certain sounds, white-noise interference should affect the naming of pictures representing objects with typical sounds leaving the naming of object without typical sounds unaffected. The results were congruent with the predictions and consistent with a view of the semantic representations of objects as collection of related representations, modal in nature, and mandatorily accessed.